The ABCs of educational testing demystifying the tools that shape our schools - Popham, W. James (Thousand Oaks, California Corwin, 2017)
Formative, data-driven, high-stakes--we all know the buzzwords surrounding educational testing. But we often shelve our understanding of these because they are overwhelmingly complex. Those who care about our schools and students--teachers, administrators, policymakers, parents, citizens--will discover how and why testing should be taken upon ourselves to advance. Using a nontechnical approach, this book offers fundamental knowledge to free you from testing fogginess--all framed around practical actions you can take to strengthen your assessment literacy. -- Amazon.com.
Why the fuss with educational testing? -- Three primary purposes of educational testing -- Behind standardized testing's cloudy curtain -- Validity: the crux of the caper -- Reliability: considering consistency in inconsistent containers -- Fairness in testing: a long time coming -- Reporting results: where rubber and road meet -- Formative assessment: instructional magic? -- Student's affect: underappreciated, undermeasured -- What next?
Includes bibliographical references (page 145) and index.
Keywords: Educational tests and measurements -- United States